Loss of Melanopsin-Expressing Ganglion Cell Subtypes and Dendritic Degeneration in the Aging Human Retina - Esquiva, Gema; Lax, Pedro; Pérez-Santonja, Juan J.; García-Fernández, José M.; Cuenca, Nicolás (Frontiers in Aging Neuroscience, 2017)
In mammals, melanopsin-expressing retinal ganglion cells (mRGCs) are, among other things, involved in several non-image-forming visual functions, including light entrainment of circadian rhythms. Considering the profound impact of aging on visual function and ophthalmic diseases, here we evaluate changes in mRGCs throughout the life span in humans. In 24 post-mortem retinas from anonymous human donors aged 10 to 81 years, we assessed the distribution, number and morphology of mRGCs by immunostaining vertical retinal sections and whole-mount retinas with antibodies against melanopsin. Human retinas showed melanopsin immunoreactivity in the cell body, axon and dendrites of a subset of ganglion cells at all ages tested. Nearly half of the mRGCs (51%) were located within the GCL, and stratified in the outer (M1, 12%) or inner (M2, 16%) margin of the IPL or in both plexuses (M3, 23%). M1 and M2 cells conformed fairly irregular mosaics, while M3 cell distribution was slightly more regular. The rest of the mRGCs were more regularly arranged in the INL and stratified in the outer margin of the IPL (M1d, 49%). The quantity of each cell type decrease after age 70, when the total number of mRGCs was 31% lower than in donors aged 30-50 years. Moreover, in retinas with an age greater than 50 years, mRGCs evidenced a decrease in the dendritic area that was both progressive and age-dependent, as well as fewer branch points and terminal neurite tips per cell and a smaller Sholl area. After 70 years of age, the distribution profile of the mRGCs was closer to a random pattern than was observed in younger retinas. We conclude that advanced age is associated with a loss in density and dendritic arborization of the mRGCs in human retinas, possibly accounting for the more frequent occurrence of circadian rhythm disorders in elderly persons.